PENGEMBANGAN ROTATIONAL DYNAMICS CONCEPTUAL SURVEY (RDCS) UNTUK MENGUKUR KONSEPSI AWAL SISWA - Anifatul Mardiyah; TantrI Mayasari; Farida Huriawati (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
DEVELOPING ROTATION DYNAMIC CONCEPTUAL SURVEY (RDCS) TO ASSESS STUDENT’S PRIOR CONCEPTIONAbstractThis study aims to develop an evaluation tool to measure the level of students' conception in the form of four-tier diagnostic test categories of material on rotational dynamics. The development model used is 3D+T. The steps of the 3D+T are: Define, Design, Develop, and Trial. The development instrument used was a validation sheet for material experts (expert judgment) and a four-tier question sheet for testing students. Validation of the feasibility of the items covering aspects of language, the suitability of the questions with cognitive aspects, and the indicator of the problem was declared very feasible to use. Instrument quality assessment is done by calculating CVR and CVI arranged in the form of a checklist column. This development research produced an RDCS (Rotational Dynamics Conceptual Survey) test instrument in the form of four tiers. The RDCS test instrument consisted of 16 items. Trials of the test instruments obtained a percentage of students' conceptions of error of 17%, misconceptions of 43%, did not understand the concept of 24%, and understood the concept of 16%.AbstrakTujuan penelitian ini adalah mengembangkan suatu alat evaluasi untuk mengukur level kategori konsepsi siswa berbentuk four-tier terhadap materi dinamika rotasi. Model pengembangan pada penelitian ini adalah 3D + T. Tahapan model pengembangan 3D+T yaitu: Define (Pendefinisian), Design (Perancangan), Develop (Pengembangan), dan Trial (Uji Coba). Instrumen pengembangan yang digunakan berupa lembar validasi oleh ahli materi (expert judgment) dan lembar soal four-tier untuk uji coba kepada siswa. Validasi kelayakan butir soal meliputi aspek bahasa, kesesuaian soal dengan aspek kognitif dan indikator soal dinyatakan sangat layak digunakan. Penilaian kualitas instrumen dilakukan dengan perhitungan CVR dan CVI disusun dengan bentuk kolom checklist. Penelitian pengembangan ini menghasilkan suatu instrumen tes RDCS (Rotational Dynamics Conceptual Survey) dengan bentuk four tier. Instrumen tes RDCS terdiri dari 16 butir soal. Uji coba instrumen tes diperoleh persentase konsepsi siswa eror sebesar 17%, miskonsepsi 43%, tidak paham konsep 24%, dan paham konsep 16%.